The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.17306/j.jard.2019.01211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multidimensional poverty in rural Adamawa State, Nigeria

Abstract: This study assessed multidimensional poverty in rural parts of Adamawa state, Nigeria. Specifically, the study objectives were to: describe the respondents’ socio-demographic characteristics, determine their multidimensional poverty status, and identify the determinants of multidimensional poverty in the sampled communities. Multi-stage cluster sampling technique was used to collect primary data from 480 household heads selected from 16 villages across the study area. Data collected were analysed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
5
0
0
Order By: Relevance
“…A household with extensive tracts of cultivated land is more likely to generate more food and is less likely to live in poverty. This result is in agreement with the study conducted by Amao et al (2017), Adepoju (2018), Michael et al (2019), and Chen (2019) et al, who found that household head farm size helps households reduce multidimensional rural poverty.…”
Section: Ordered Logit Regression Results On the Determinants Of Mult...supporting
confidence: 93%
See 3 more Smart Citations
“…A household with extensive tracts of cultivated land is more likely to generate more food and is less likely to live in poverty. This result is in agreement with the study conducted by Amao et al (2017), Adepoju (2018), Michael et al (2019), and Chen (2019) et al, who found that household head farm size helps households reduce multidimensional rural poverty.…”
Section: Ordered Logit Regression Results On the Determinants Of Mult...supporting
confidence: 93%
“…This outcome supports the findings of Michael et al (2019), according to which the likelihood of being poor increases with being a female-headed household (rather than a male headed household). Family size is significantly and negatively correlated with multidimensional poverty status.…”
Section: Ordered Logit Regression Results On the Determinants Of Mult...supporting
confidence: 87%
See 2 more Smart Citations
“…Decomposing for gender based on the four‐dimension (as shown in Table 8) revealed that children from the male‐headed household are less likely to be educationally deprived, less likely to have a better living standard, less likely to have health‐related issues, and 1% more likely to have access to the internet than female‐headed household. These results correspond to those of Fonta et al (2018), White and Yamasaki (2017), and Michael et al (2019).…”
Section: Resultssupporting
confidence: 92%